2021
DOI: 10.1007/jhep11(2021)148
|View full text |Cite
|
Sign up to set email alerts
|

Towards high-precision parton distributions from lattice QCD via distillation

Abstract: We apply the Distillation spatial smearing program to the extraction of the unpolarized isovector valence PDF of the nucleon. The improved volume sampling and control of excited-states afforded by distillation leads to a dramatically improved determination of the requisite Ioffe-time Pseudo-distribution (pITD). The impact of higher-twist effects is subsequently explored by extending the Wilson line length present in our non-local operators to one half the spatial extent of the lattice ensemble considered. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 108 publications
1
17
0
Order By: Relevance
“…The distillation framework [61] is a further example of smearing with the important benefit that it enables a momentum projection to be performed at each point in a two-point or three-point function, thereby providing a more complete sampling of the lattice than is possible with the Jacobi or Wuppertal frameworks. The efficacy of combining the more complete sampling of the lattice made possible by distillation with the ability to reach higher momenta using momentum smearing [62] has been demonstrated in the recent calculation of the unpolarized PDF using distillation [63], which showed improved precision in comparison with an earlier work employing Jacobi smearing [64].…”
Section: Methods For Signal-to-noise Improvementmentioning
confidence: 99%
“…The distillation framework [61] is a further example of smearing with the important benefit that it enables a momentum projection to be performed at each point in a two-point or three-point function, thereby providing a more complete sampling of the lattice than is possible with the Jacobi or Wuppertal frameworks. The efficacy of combining the more complete sampling of the lattice made possible by distillation with the ability to reach higher momenta using momentum smearing [62] has been demonstrated in the recent calculation of the unpolarized PDF using distillation [63], which showed improved precision in comparison with an earlier work employing Jacobi smearing [64].…”
Section: Methods For Signal-to-noise Improvementmentioning
confidence: 99%
“…In Ref. [105], it was found that discretization effects lead to the violation of the DGLAP evolution of PDFs. The authors of the aforementioned work only used a single lattice spacing, but parametrized the cutoff effects using Jacobi polynomials under the assumption that they have the form a/|z| multiplied by a function of ν.…”
Section: Compatibility With Dglap Evolutionmentioning
confidence: 99%
“…We recall here the methodology of this test proposed in Ref. [105]. It consists of fitting the real part of ITDs at fixed z to a cosine Fourier transform of a phenomenologically-inspired ansatz for the valence PDF:…”
Section: Compatibility With Dglap Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LaMET and SDF approaches provide complementary methods for extracting PDFs from lattice calculations, with different systematic uncertainties. The success of these approaches has encouraged significant effort aimed at constraining PDFs through lattice QCD, using a variety of methods and lattice actions [48,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. These methods generally provide more information about PDFs than does the traditional approach of calculating the Mellin moments of PDFs from matrix elements of local operators.…”
Section: Introductionmentioning
confidence: 99%